2015
DOI: 10.17265/2162-5298/2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Modulating a Solar Parabolic Dish to Produce Boiled Water

Abstract: A two-meter parabolic solar concentration dish has been modulated to produce boiled water over 100 o C for various purposes of central heating services. For an effective performance, the system required both continuous exposure of the dish to sunlight during the day time as well as to an electric control circuit (tracking system). The amount of the potable water was dependent particularly on the accurate centering of the system which could increase upon preheating. This system has therefore been possible to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Figures (8) shows a increasing in heat loss coefficient by convection with increasing wind speed because receiver temperature decresing The heat moves around the boiler into the atmosphere this result agree with resercher. When low speed wind the temperatuer of boiller is too high like( black bady Radiation) the flow rate of water is low so as the heat travels to the water and rises rapidly until it turns into steam , thus increasing of the heat transfer as shown in Figure (9) this result agree with resercher [12,13].…”
Section: Table (1) Characterization Of Array Concentrationsupporting
confidence: 74%
See 1 more Smart Citation
“…Figures (8) shows a increasing in heat loss coefficient by convection with increasing wind speed because receiver temperature decresing The heat moves around the boiler into the atmosphere this result agree with resercher. When low speed wind the temperatuer of boiller is too high like( black bady Radiation) the flow rate of water is low so as the heat travels to the water and rises rapidly until it turns into steam , thus increasing of the heat transfer as shown in Figure (9) this result agree with resercher [12,13].…”
Section: Table (1) Characterization Of Array Concentrationsupporting
confidence: 74%
“…The simulation of dish collector is done in mat lab software" [7]. "A parabolic solar concentration dish has been modulated to solar water heater up 100 o C for an effective performance, the system required both continuous exposure of the dish to sunlight during the day time [8]. "Analysis Methodology developed for a PDSC system used for heating thermic fluid for process heating application.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the sufficient heat stored within the peak hours of solar radiation. A research [23] has reported the possibility of a proportional increase in solar irradiation with time, and could attain its intensity during the midday between 12:00–14:00 (peak hours).
Fig.
…”
Section: Methods Validationmentioning
confidence: 99%